The role of ecological innovation and ecological marketing towards green marketing performance improvement - Harini, Cicik; Priyanto, Sony Heru; Ihalauw, John J. O. I.; Andadari, Roos Kities (Management and Entrepreneurship: Trends of Development, 2020)
This research contributes to efforts to improve marketing performance in batik small and medium enterprises that care about the sustainability of the ecosystem through ecological innovation and ecological marketing. This paper discusses the results of a study of the relationship between marketing and the willingness to support environmentally friendly among small-scale ‘batik’ (Indonesian traditional clothing) producers in Central Java. The study was conducted on natural color batik SMEs in Central Java with a total sample of 120 respondents obtained through non-probability sampling to test the relationship between variables that developed in this study, using SEM-PLS modeling. The findings suggest that the performance of green marketing can be enhanced by ecological innovation through intervening variables of ecological marketing. The study found that operators with higher marketing performance measured by customer growth, market share and sales volume were more willing to replace synthetic dyes with more environmentally friendly natural dyes, even though the price of batik products was more expensive. The increased performance of green marketing in this study, it is expected to be able to encourage batik SMEs who use synthetic dyes to switch to natural dyes to reduce environmental pollution and protect the world from degradation through sustainable consumption and production. JEL Classification: Z1, K3, L5, L8